Gut microbiota in reintroduction of giant panda. Issue 2 (6th January 2020) - Tang, Jingsi; Wang, Chengdong; Zhang, Hemin; Zhao, Jiangchao; Guo, Wei; Mishra, Sudhanshu; Kong, Fanli; Zeng, Bo; Ning, Ruihong; Li, Desheng; Yang, Jiandong; Yang, Mingyao; et al.
Abstract: Reintroduction is a key approach in the conservation of endangered species. In recent decades, many reintroduction projects have been conducted for conservation purposes, but the rate of success has been low. Given the important role of gut microbiota in health and diseases, we questioned whether gut microbiota would play a crucial role in giant panda's wild‐training process. The wild procedure is when captive‐born babies live with their mothers in a wilderness enclosure and learn wilderness survival skills from their mothers. During the wild‐training process, the baby pandas undergo wilderness survival tests and regular physical examinations. Based on their performance through these tests, the top subjects (age 2–3 years old) are released into the wild while the others are translocated to captivity. After release, we tracked one released panda (Zhangxiang) and collected its fecal samples for 5 months (January 16, 2013 to March 29 2014). Here, we analyzed the Illumina HiSeq sequencing data (V4 region of 16S rRNA gene) from captive pandas ( n  = 24), wild‐training baby pandas ( n  = 8) of which 6 were released and 2 were unreleased, wild‐training mother pandas ( n  = 8), one released panda (Zhangxiang), and wild giant pandas ( n  = 18). Our results showed that the gut microbiota of wild‐training pandas is significantly different from that of wild pandas but similar to that of captive ones. The gut microbiota of the released panda Zhangxiang gradually changed to become similar to those of wild pandas after release. In addition, we identified several bacteria that were enriched in the released baby pandas before release, compared with the unreleased baby pandas. These bacteria include several known gut‐health related beneficial taxa such as Roseburia, Coprococcus, Sutterella, Dorea, and Ruminococcus . Therefore, our results suggest that certain members of the gut microbiota may be important in panda reintroduction. Abstract : The gut microbiota of wild‐training pandas is significantly different from that of wild pandas, but similar to that of captive ones. However, the gut microbiota of panda Zhangxiang gradually changed to that of wild pandas after successful release. Several bacteria that were enriched in the wild‐training baby pandas who met the criteria for release into the wild. These bacteria include several known gut‐health‐related beneficial taxa such as Roseburia, Coprococcus, Sutterella, Dorea, and Ruminococcus, indicating potential roles of these bacteria in the fitness of these baby pandas.